Lectotypification of four names in the genus Capparis (Capparaceae) - Maurya, Satish; Datar, Mandar N.; Choudhary, Ritesh Kumar (Phytotaxa, 2021)
The genus Capparis Linnaeus (1753: 503) belongs to the family Capparaceae and is distributed in tropics and subtropics of the Old World, comprising 141 species (POWO 2021). Jacobs (1965) studied the genus from Indus to pacific land and classified it under four formal sections viz. Capparis, Sodada, Monostichocalyx, and Busbeckea. Thereafter, several new species were described under the genus from various parts of the Old World (Srisanga & Chayamarit 2004, Fici 2012, Huang et al. 2013, Thuong et al. 2013, 2015, 2017a,b, 2018, 2020, Fici et al. 2020, Murugan et al. 2020).